Pengenalan Budaya Dan Pembentukan Karakter Melalui Folklor Pada Anak Usia Dini - Winda Dwi Hudhana (Fakultas Tarbiyah dan Ilmu Keguruan IAIN Purwokerto, 2015)
Abstract: Indonesia is a country rich with diversity of race, traditions, and, culture. However, this diversity is gradually shifted as to the progress of science and technology. Thus, the need for the introduction of the culture, one through folklore to future generations so that continuity is maintained. In addition, folklore have good character learning, considering the character degradation of today’s young generation. The good characters portrayed in folklore can be taught to early childhood. Introduction to the culture and character formation through folklore can use three methods of storytelling, re-storytelling, and theater or drama. These methods for early childhood learning can be done by parents and teachers. Keywords: character education, folklore, storytelling.